Edge transport in the trivial phase of InAs/GaSb. (28th July 2016) - Nichele, Fabrizio; Suominen, Henri J; Kjaergaard, Morten; Marcus, Charles M; Sajadi, Ebrahim; Folk, Joshua A; Qu, Fanming; Beukman, Arjan J A; Vries, Folkert K de; Veen, Jasper van; Nadj-Perge, Stevan; Kouwenhoven, Leo P; et al.
Abstract: We present transport and scanning SQUID measurements on InAs/GaSb double quantum wells, a system predicted to be a two-dimensional topological insulator. Top and back gates allow independent control of density and band offset, allowing tuning from the trivial to the topological regime. In the trivial regime, bulk conductivity is quenched but transport persists along the edges, superficially resembling the predicted helical edge-channels in the topological regime. We characterize edge conduction in the trivial regime in a wide variety of sample geometries and measurement configurations, as a function of temperature, magnetic field, and edge length. Despite similarities to studies claiming measurements of helical edge channels, our characterization points to a non-topological origin for these observations.